PENGARUH PENGUNGKAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN - Dwi Kartikasari; Nur Salina (Politeknik Negeri Batam, 2017)
This study aims to determine the relationship between items in the disclosure of Corporate Social Responsibility (CSR) to profitability The company measured through Return On Assets and Net Profit Margin. Data analysis method used in this research is data panel regression. Data used in this research is secondary data by analyzing annual report and company financial report in 2014 and 2015. The result of research indicate that there is only one item of CSR that have significant influence Against Return On Assets (ROA) is an indicator of social society. While for the NPM variable there are only environmental performance indicators that have a significant influence on Net Profit Margin (NPM).